2012
DOI: 10.1002/app.38419
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal aging mechanisms of aramid fibers via synchrotron small‐angle X‐ray scattering and dynamic thermal mechanical analysis

Abstract: In this study, synchrotron small-angle X-ray scattering (SAXS) and dynamic mechanical thermal analysis (DMTA) were used to evaluate the aging behavior of microfibrils and nanovoids. The effects of such structures on the tensile strength were also investigated. We investigated the correlation length of the fibril interface by fitting the SAXS intensity using the Debye-Bueche method. The orientation and size of the voids were determined with Ruland's streak method. The results show that the correlation length de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Besides, numerous experimental studies or recent works on molecular‐level computations done by Grujicic et al have reported on the complexity of the hierarchical microstructure of the Kevlar fiber. The manufacturing process implies local gradient of shear rates and also complex kinetics of both cooling and solvent evaporation that modify the structure at the fiber diameter scale.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, numerous experimental studies or recent works on molecular‐level computations done by Grujicic et al have reported on the complexity of the hierarchical microstructure of the Kevlar fiber. The manufacturing process implies local gradient of shear rates and also complex kinetics of both cooling and solvent evaporation that modify the structure at the fiber diameter scale.…”
Section: Introductionmentioning
confidence: 99%
“…Voids affect the mechanical properties of the fibers, namely, they tend to decrease the tensile strength 58,59,131 . The PPTA fabrics capacity to absorb water and ability to take up dyestuff are very low compared to other fabrics 130 .…”
mentioning
confidence: 99%
“…As a result, hydrothermal aging has become one of the most important mechanisms threatening the structural integrity of GFRP composites . Numerous experimental studies and daily experience have demonstrated that long‐term exposure to elevated temperatures and high moistures inevitably leads to localized stresses . Nonuniform stress distributions greatly affect the initiation and propagation of microcracks and thus degrade the performance of GFRP composites .…”
Section: Introductionmentioning
confidence: 99%